Teacher’s Perception on Implementing Differentiated Learning in Vocational High School (SMKN) Gowa - Israyani Masyita; Muhammad Tahir; Nur Aeni (International Journal of Language, Education, and Literature, 2026)
This study was designed to evaluate more about the teacher’s perception on implementing Differentiated Instruction in Vocational High School (SMKN) Gowa using qualitative approach. Four research instruments were used to collect data in this study involves classroom observation, questionnaires, and interviews. The participant of this research were  English teachers of Vocational      High School (SMKN) in Gowa, South Sulawesi, which were consist of five representatives’ teachers from each Vocational High School in Gowa. There are: SMKN 1, SMKN 2, SMKN 3, SMKN 4, SMKN 5 Gowa. Qualitative data was analyzed by using the Thematic Analysis (TA) criteria. Document analyses and classroom observations were utilized to gather data on the actual practices of teachers regarding differentiated instruction (DI). Concurrently, a questionnaire was administered to collect information on teachers' perceptions and practices related to DI. Additionally, interviews were conducted to assess teachers' views on DI. The findings of the study revealed that most of the teacher’s agreed that Differentiated Instruction (DI) has many positive outcomes, such as increased student engagement, equitable learning opportunities, addressing individual needs, fostering a sense of belonging, inspiring students to achieve their maximum potential, and enhancing student’s motivation. Meanwhile, all the teachers stated that Differentiated Instruction adoption could be difficult to be implemented because of its time requirements, difficulty with increased class sizes, differing teacher approaches, and difficulty fitting DI into regular classroom procedures.Teacher’s perspective in implementing differentiated learning in line with the Kurikulum Merdeka at Vocational High School in Gowa is the wide range of student abilities. Not all students are ready for a more flexible approach, so they sometimes need time to adapt to the method. In addition, limited resources—such as teaching materials suited to students’ needs—hinder effective differentiated instruction.